Karakteristisasi dan Profil Biodegradasi Material Biokomposit Bovine Hidroksiapatit (Bha)/Ampas Kopi/Shellac - Taufiq Hidayat; Joko Triyono; Abu Masykur (Mekanika: Majalah Ilmiah Mekanika, 2018)
The incidence of fractures in Indonesia is quite high so it needs biomaterials in the field of health that is economical and environmentally friendly. Bovine bone waste can be used for grafting, repairing, replenishing or replacing bones and restoring dental tissue. The purpose of this research is to determine whether the content of the coffee grounds and shellac will disappear after the sintering process, and how the effects of coffee grounds on the porosity and degradation rate of BHA biocomposite materials. This research uses heating method of calcination and sintering. Based on the analysis of test data conducted, it was concluded that SEM EDX observation shows the presence of inorganic elements of Ca and P with high intensity and Na, Mg, O and C with low intensity. Observation of XRD diffraction pattern shows 2θ values of the sample according to the standard diffraction pattern of HA JCPDS 9-432. FTIR functional group analysis showed no major peak points other than phosphate functional groups ( ), carbonates ( ) and hydroxyl (OH-). From these three observations indicate that the content of coffee and shellac dregs has disappeared completely when the sintering process and leaving only the content of BHA and the more mixture of coffee dregs used will decrease the density value and increase the number of porus and accelerate the degradation rate.